2019
DOI: 10.4168/aair.2019.11.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cutaneous Adverse Reactions in Korean Pediatric Patients: A Study From the Korea SCAR Registry

Abstract: Purpose Although severe cutaneous adverse drug reactions (SCARs) are rare, they are associated with high morbidity and mortality, and thus early diagnosis and treatment are critical for improving prognoses. However, few studies have reported the characteristics of SCARs in children. Thus, we aimed to evaluate the clinical characteristics, current management and prognosis of pediatric SCARs. Methods We analyzed pediatric data in the Korean SCARs registry, which was built… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
3
16
1
1
Order By: Relevance
“…Although SCARs can be caused by a diverse group of drugs, in this study, the most frequent culprits were the aromatic anticonvulsants drugs. This is in contrast to what was found in otherstudiesthat evaluated SCARs when antibiotics were the predominant responsible drugs [21,22,24,25]. This could be due to the fact that there were a higher number of patients with DRESS-DiHSreported in the present study, in which the use of antiepileptic drugs was predominant.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Although SCARs can be caused by a diverse group of drugs, in this study, the most frequent culprits were the aromatic anticonvulsants drugs. This is in contrast to what was found in otherstudiesthat evaluated SCARs when antibiotics were the predominant responsible drugs [21,22,24,25]. This could be due to the fact that there were a higher number of patients with DRESS-DiHSreported in the present study, in which the use of antiepileptic drugs was predominant.…”
contrasting
confidence: 99%
“…Several pharmacogenomics studies carried out in the Asian and European population [29][30][31] Otherstudies have shown that bacterial infections were the second most common underlying condition that indicated the use of these antibiotics. This result is consistent with previous studies [21,24]. Allopurinol has been another medication frequently implicated in SCARs, [3,22]; however, in our study, it has been identified as a potential cause of SCARs in 6 patients (8.6%); 3 of them with TEN, 2 with DRESS or DIHS and one with AGEP.Fifty-three patients (75.7%) were exposed to only one suspected drug, 17 patients (24.2%) received two or more drugs, the additional drugs having a much lower risk of causing SCARs.…”
supporting
confidence: 94%
“…However, some findings are consistent across all SCARs: a certain period must pass before SCARs become fullblown, and early drug withdrawal and supportive care with antiinflamma tory medication is the management of choice. 26,27) In our previous study based on the Korean SCARs registry, we analyzed 47 pediatric cases of DRESS, SJS, and TEN from 15 tertiary hospitals. 27) The latency period between drug exposure and symptoms was longest in DRESS patients (mean, 23.5 days) and shorter in SJS and TEN patients (mean, 4 and 6.5 days, res pectively).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…26,27) In our previous study based on the Korean SCARs registry, we analyzed 47 pediatric cases of DRESS, SJS, and TEN from 15 tertiary hospitals. 27) The latency period between drug exposure and symptoms was longest in DRESS patients (mean, 23.5 days) and shorter in SJS and TEN patients (mean, 4 and 6.5 days, res pectively). Cutaneous lesion extent was largest in DRESS cases without mucosal involvement in most cases and without per manent sequelae in all cases.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation